Laura Shapiro: What She Ate. Six Remarkable Women & the Food That Tells Their Stories - Wilkins, John (Petits Propos Culinaires, 2018)
Laura Shapiro: What She Ate. Six Remarkable Women & the Food That Tells Their Stories: 4th Estate, 2018: 307 pp., hardback, £14.99.